2014
DOI: 10.1111/bjd.13479
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and photodermatoses

Abstract: ORIGINAL ARTICLE, p 1478

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The mechanism by which UVR photohardening increases the level and function of Tregs may involve the production of vitamin D. Indeed, its supplementation has been shown to be associated with significantly increased numbers of Tregs in apparently healthy individuals . That said, a previous study from our laboratory has indicated that 311‐nm UVB hardening was capable of increasing serum 25‐hydroxyvitamin‐D3 levels which may be low in patients with photosensitivity and cases of photodermatoses, including PLE …”
Section: Discussionmentioning
confidence: 95%
“…The mechanism by which UVR photohardening increases the level and function of Tregs may involve the production of vitamin D. Indeed, its supplementation has been shown to be associated with significantly increased numbers of Tregs in apparently healthy individuals . That said, a previous study from our laboratory has indicated that 311‐nm UVB hardening was capable of increasing serum 25‐hydroxyvitamin‐D3 levels which may be low in patients with photosensitivity and cases of photodermatoses, including PLE …”
Section: Discussionmentioning
confidence: 95%
“…Diagnosis can be confirmed with phototesting, which reveals reduced minimal erythemal doses (MEDs), especially in the ultraviolet B (UVB) and shorter ultraviolet‐A (UVA) wavelengths 6 . In some cases, phototesting can demonstrate an abnormal response to visible light (VL) 7 . While the exact prevalence is unknown, newly emerged studies have reported an increase in the frequency of CAD in the skin of color population, particularly among African Americans (AAs) 8 …”
Section: Introductionmentioning
confidence: 99%
“…6 In some cases, phototesting can demonstrate an abnormal response to visible light (VL). 7 While the exact prevalence is unknown, newly emerged studies have reported an increase in the frequency of CAD in the skin of color population, particularly among African Americans (AAs). 8 The aim of this study was to evaluate patients diagnosed with PMLE and CAD during a 23-year period in our photomedicine center, and investigate differences in demographic, clinical, and photobiological features between patients with light and dark skin types.…”
mentioning
confidence: 99%